Tuning photoluminescence of Ge/GeO2 core/shell nanoparticles by strain - Yuan, C. L. (2012)
The distribution of strain field plays an important role in deciding the physical properties of nanocrystals. The growth strain of Ge/GeO2 core/shell nanoparticles embedded in a regular array of Al2O3 nanoparticles and its resulting effect on the optical properties are investigated. Two-dimensional finite element calculations clearly demonstrate that Ge/GeO2 nanoparticles certainly experienced greater compressive strain in Al2O3 nanoparticles than in Al2O3 thin film, especially at the GeO2 shell area. This may lead to much more strain-relaxing defects produced at the GeO2 shell in Al2O3 nanoparticles. Meanwhile, the photogenerated excitons/electron−hole pairs are localized by defects located at the GeO2 shell and are forced to recombine while being spatially confined in the Al2O3 nanoparticles. These effects might contribute to the observed intensity enhancement and blue shift of the photoluminescence peaks for the sample with Ge/GeO2 core/shell nanoparticles embedded in Al2O3 nanoparticles. The findings presented here provide physical insight and offer useful guidelines to controllably modify the optical properties of semiconductor nanoparticles through strain engineering.